Innovations in technology dissemination (ITD): in Kannur distrcit - Namitha Reghunath (Department of Agricultural Extension, College of Agriculture, 2016)
The present study entitled “Innovations in Technology Dissemination (ITD): in Kannur district” was carried out with the objectives; to document the Innovations in Technology Dissemination (ITD) methods implemented by different agricultural institutions in Kannur district with special reference to Kannur KVK, to find out the effectiveness and farmers perception towards these approaches, to study the constraints and suggest effective ITD method for technology transfer. Thirty farmers each from four selected grama panchayats of Kannur district were identified using simple random sampling and a total of one hundred and twenty respondents were included in the study. A well-structured interview schedule was used for collecting the data from the respondents. Two dependent variables and sixteen independent variables were studied and analysed with the help of different statistical tools. The findings indicate that Compact Area Group Approach (CAGA), farmers science museum, farmers science congress, NABARD- KVK farmers club, agro- biopharmacy, mussel farmers club, KVK mall, creative extension activities etc. were the important Innovations in Technology Dissemination (ITD) methods implemented by Kannur KVK. ATMA (Agricultural Technology Management Agency), LEADS (Lead farmer centered Extension Advisory and Delivery Services), ATMA PLUS, training programmes by Department of Agriculture, crop health management scheme, Innovations by Non Governmental Organisations (NGOs), farmers clubs formed by different banks were the ITD methods implemented by other agricultural institutions in Kannur district. On analysis of data, it was found that majority of the farmers (64.16%) belonged to old age group and had regular contact with Agricultural Officers(75.83%), Assistants(76.67%) and Bank Officials (64.17%). Most of the respondents had medium level of economic motivation (85%), decision making ability (69.17%), innovation proneness (65.83%), acceptance of innovation (54.17%), participation efficiency (56.67%), group interaction (67.5%) and need satisfaction (69.17%). Majority of the farmers (62.5%) had medium level of perception on ITD methods however, most of the respondents were not aware of the different ITD methods implemented by Kannur KVK and other agricultural institutions in Kannur district. Perception and extent of awareness of farmers on ITD methods were positively and significantly correlated with mass media exposure, extension agency contact, extension participation, social participation, innovation proneness, acceptance of innovation, participation efficiency, group interaction and need satisfaction. Lack of awareness about the latest ICT (Information and Communication Technology) methods for technology dissemination, ineffective training programmes, inadequate trainings for farmers and extension personnels, unavailability of technologies on time, irregularity in conducting farmers group meetings etc. were the important constraints of the existing ITD methods. The suggestions put forth by the farmers were, starting of training centres at each panchayats, providing training programmes to youth, providing trainings on ICT tools in technology dissemination and the like to improve the existing methods. The study revealed that, to increase the awareness and farmer’s perception on ITD methods, there should be an integrated approach with inclusion of farmer led technologies in the dissemination process, technology transfer through participation of farmer groups and development of an ideal system combining conventional and latest ICT based methods for technology dissemination.